Prevalence of obesity in prepubertal and pubertal with Turkish population type 1 diabetes - Özkaya, Volkan; Eren, Erdal; Özgen Özkaya, Şebnem; Denkboy Öngen, Yasemin (Springer Japan K.K., 2021)
To determine the prevalence of prepubertal and pubertal obesity in children and adolescents with type 1 Diabetes Mellitus (Type 1 DM). One hundred fifty children and adolescents aged 6-18 years with Type 1 DM who attended the Pediatric Endocrinology Polyclinic and were diagnosed with type 1 DM were included in the study. Tanner staging was used to estimate pubertal status. Age- and gender-specific body mass index (BMI) percentile between 85 and 95% was accepted as overweight and > 95% as obese. It was determined that the overweight prevalence rates in children and adolescents with type 1 DM were 13.3% and the obesity rate was 14.3%. It was found that while the overweight prevalence rates (14.1%) were higher in males, the obesity prevalence was higher in females (19.0%). The obesity prevalence rates at the prepubertal and pubertal stages were found to be 17.1% and 13.8%, respectively. The obesity prevalence at the pubertal stage was higher in girls (22.4%) than boys (3.9%) (p < 0.05). The rates both of overweight and obesity in boys decreased from prepubertal to pubertal periods, while those rates increased in girls. Our results indicated that the obesity prevalence in prepubertal and pubertal children and adolescents with type 1 DM was higher compared to healthy peers in the literature. The authors believe that the risk factors for obesity in this population should be determined and obesity-prevention programs for diabetes should be prepared.
Keywords: Obesity; Overweight; Prepubertal; Pubertal; Type 1 Diabetes